Anies Baswedan's Political Communication: Ferdinand De Saussure's Semiotic Analysis of the Event Using Anies Ambon - Sofiyatul Laily Badriyah; Khomsiyatul Mukarromah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The 2024 Indonesian presidential election is a crucial moment in political communication, with each candidate employing various campaign tactics to enhance their reputation and win public favor. The